Gap Analysis on Sustainable Supply Chain Model Derived from EU RED II and Ispo 2015 - Aninda Annisa; Yuanita Handayati (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Garut, 2020)
Palm oil today is consumed not only for health, cooking, and other daily product but also converted into biodiesel. The EU has included the use of biodiesel as part of their clean energy for transportation and one of its sources is palm oil. However, with the release of the EU RED II, the food and feedstock used for biodiesel are selected more stringent today. The EU requires the food and feedstock sourced for biodiesel to be categorized as low indirect land-use change (ILUC) risk and those categorized as high ILUC-risk shall be gradually phased out to 0% by 2030. This provision applies to Indonesia’s palm oil making the two countries come to file a dispute to the World Trade Organization (WTO). This paper aims to analyze the lacking of Indonesia’s palm oil sustainable cultivation measures that make Indonesia’s palm oil usage in the EU threatened to be phased out to 0% by 2030. With an extensive literature review and analysis of the two law products, this paper is analyzing the gap between the EU regulation and the ISPO certification system. It is found that there are 16 main points of difference highly concentrated on carbon emission calculation mismatch. In the end, this paper is proposing a new SCOR to be implemented in Indonesia palm oil cultivation while adjusting to its condition to ensure the low ILUC-risk and pursue the trade with the EU as the second biggest market for palm oil in the world.